Load Balancing Based on Multimedia Task Division for Reactive WSNs: Case Study for Pest Management - Souza, Weslen S.; de Brisolara, Lisane Brisolara; Ferreira, Paulo R. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2022: Anais do XII Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2022)
Wireless Sensor Networks have been widely used for monitoring and data collection. Technological advances allowed the integration of multimedia devices into these networks, giving rise to new possible applications. The nodes that make up these networks are commonly located in external environments where they are exclusively powered by batteries, thus the network lifetime depends on the charge of these batteries. To maximize the useful life of the network as a whole, load balancing techniques are proposed with the aim of promoting a more homogeneous energy consumption by all the nodes, preventing only a few nodes from working in excess and dying prematurely. Most of the studies identified in the literature for reactive WSN only address networks with overlapping sensing, making the decision of which of the nodes that detected this same event should process it. In this work, networks without sensing overlap are addressed, where a load balancing strategy based on task division is proposed. An event is split into several smaller multimedia processing subtasks, which are distributed to neighboring nodes that are able to perform the processing. Through experiments, we show the improvements of around 29% achieved by the proposed approach, when compared to a WSN that does not use any load balancing technique.